Morphological Analysis on Cranberry Morpheme Found In Mark Twain’s Selected Works - Raflis Raflis; Mailiani Mailiani (Jurnal Ilmiah Langue and Parole, 2020)
This research uses descriptive qualitative research which aimed to find the cranberry morphemes and the applications in Mark Twain’s selected works entitled The Adventures of Tom Sawyer and The Adventures of Huckleberry Finn. Cranberry morpheme is a morpheme that occurs in only one word and it can be thought of as a bound root that occurs in only one word. The bound roots are often foreign borrowings that were free in the source language, but not free in English. Documentation method used to collect the data. Translational identity method used to analyze the data because the research involves other language which is Latin. Some theories are employed to analyze the data, such as Carstairs-McCarthy (2002) and Denham (2010). The result shows that there are 12 Latin-derived cranberry morphemes found:-ceiv, –sum, -mit, -duc, -serv, -scrib, -tain, -fer,-vert, -ced, -lat, and –vok which -ceiv is the dominance and 3 non-Latin-derived cranberry morphemes found: twi-, -kemp and hap- which twi- is the dominance. The applications of cranberry morphemes occur with and without affix which are suffixes -ed, -er, -ing, and -s. The suffix -ed is the most frequently used suffix of the cranberry morpheme application.